Low Carbohydrate Diets in Cancer Therapeutics: Current Evidence - Haskins, Christopher; Cohen, Justin; Kotecha, Rupesh; Kaiser, Adeel (Frontiers in Nutrition, 2021)
Low carbohydrate diets have a promising mechanistic rationale in the treatment of cancer with favorable preclinical data. The strongest data suggest synergistic effects of dietary interventions with traditional cancer therapies. Recent prospective clinical trials suggest that low carbohydrate diets are safely and feasibly added within a busy oncology clinic, with hopeful additive effects in treatment enhancement.